Problems of shrimp entrepreneurs in Tamil Nadu - K. Ponnusamy,; S.M.Pillai,; C.Sarada, (Journal of Agricultural Extension Management, 2025)
Aquaculture contributes significantly to foreign exchange earnings, food production and employment generation. The profitability of shrimp farming is relatively high, as the entrepreneurs are able to realise their investment in a couple of years. However, the present situation is considered to be highly volatile due to serious setbacks in shrimp farming, due to disease outbreaks, judicial pronouncements, government apathy, environmental misapprehensions, over cautious attitude of financial institutions, bureaucratic indifference and non-cooperation among farmers with regard to local common resource management. If the potential and contribution of ·aquaculture are to be realised, issues and challenges faced by the entrepreneurs need to be studied and analysed. Hence, a research study was undertaken to assess the social, economic, psychological and technological problems at different stages starting from planning to marketing as perceived by the shrimp entrepreneurs